Depicting Love - Badia, Montse; Künstlerhaus Bethanien, Berlin (Berlin München : Künstlerhaus Bethanien Berlin Philip Morris Kunstförderung München, 2004)
Alvargonzalez, Chema ; Anson, Marti ; Gomulicki, Maurycy ; Held, Oliver ; Ikemura, Leiko ; Kaufmann, Andreas M. ; Palacin, Mabel ; Philipsz, Susan ; Ruiz, Francesc ; Rothuizen, Jan ; Samore, Sam ; Young-Hae Chang Heavy Industries
DVD in speciale kast
Biog. [1 p.]
Publication on the occasion of the exhibition 'Depicting Love' at Künstlerhaus Bethanien in Berlin, 17.06.2004 - 24.06.2004
boek